The spatial spillover effects of establishing free trade pilot zones on FDI: Empirical evidence from China - Tingting Zhang; Wenxuan Wang (Heliyon, 2023)
The establishment of free trade pilot zones (FTZs) in China has constituted a pivotal endeavor to enhance global collaboration, foster economic restructuring and transformation, and attract foreign direct investment (FDI). These objectives are pursued through a series of strategies, including implementing a negative list system, reducing the threshold for FDI, and enhancing the FDI service framework. Based on panel data from 47 cities between 2005 and 2018, this research employs a spatial difference-in-differences model to empirically examine the spatial spillover effects of establishing FTZs concerning FDI. The findings reveal the substantial positive impact of FTZs on fostering FDI within respective domains. Conversely, an adverse spillover effect is observed on FDI in neighboring vicinities. Coastal FTZs have a negative spillover effect on FDI in surrounding areas, whereas inland FTZs have minimal impact on FDI in surrounding areas. The first and third batches of FTZs have had negative spillover effects on FDI in surrounding areas, while the second batch of FTZs has had no significant spatial spillover effect on FDI. Based on the empirical conclusions, this study proposes policy recommendations to broaden the scope of FTZs, refine the spatial spillover mechanism, and foster the diversified development of FTZs. These measures are envisaged to optimize the efficacy of the FTZ strategy to advance FDI objectives.